2022
DOI: 10.1080/00220388.2022.2094253
|View full text |Cite
|
Sign up to set email alerts
|

Digital Divide or Digital Provide? Technology, Time Use, and Learning Loss during COVID-19

Abstract: Data used in this study has been collected as part of a purposefully designed survey, conducted during 5-28 May 2020. Data was collected through a rapid response telephone survey. Feature phone ownership is universal in Bangladesh, at least at a household level. So, we are not concerned about technology (including smartphone access) related sample selection into our study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…The gender differences in home study participation reported by Plan International (2020) are descriptive statistics obtained through small‐scale research. Similarly, Asadullah and Bhattacharjee's (2022) findings related to all forms of home study, rather than to EdTech alone, and were specific to Bangladeshi slum and rural households. Mathrani et al's (2021) convenience sample provided gender difference information collected on child EdTech perspectives, but not usage.…”
Section: Literature Reviewmentioning
confidence: 94%
See 4 more Smart Citations
“…The gender differences in home study participation reported by Plan International (2020) are descriptive statistics obtained through small‐scale research. Similarly, Asadullah and Bhattacharjee's (2022) findings related to all forms of home study, rather than to EdTech alone, and were specific to Bangladeshi slum and rural households. Mathrani et al's (2021) convenience sample provided gender difference information collected on child EdTech perspectives, but not usage.…”
Section: Literature Reviewmentioning
confidence: 94%
“…5 Even when infrastructural requirements are satisfied, however, non-structural barriers still have to be overcome. Mere household ownership of a technology that can access EdTech does not necessarily translate to more child learning time (Asadullah & Bhattacharjee, 2022). 6 Children's access to EdTech tools is shaped by their caregivers (Genc, 2014), who influence whether a given learning material-digital or otherwise-is used (Rideout et al, 2003) and in what proportions (Kucirkova et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations